Pengaruh Komitmen Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Petrolog Indah Badak - Satryawati Satryawati; Andi Nurhasanah; Risma Wati (Politeknik Negeri Samarinda, 2020)
This study aims to conclude whether or not there is an influence of organizational commitment and job satisfaction on employee performance at PT. Beautiful Rhino Petrologist. Data processing in this study used SPSS 23 for windows software, while testing was carried out by simultaneous and partial testing. After analyzing the data obtained from the respondents, the researcher concludes that organizational commitment and job satisfaction both simultaneously and partially have an effect on employee performance. In multiple linear regression, organizational commitment and job satisfaction have a positive influence on employee performance.